Literature Review Factors Affecting Employee Performance As Human Resources - Rosa Indah Parawansah; Sudarmiatin Sudarmiatin (Universitas 45 Surabaya, 2024)
This study presents a review of the factors that can affect employee performance as human resources, this study has the aim of building hypotheses to be used in further research. Previous studies or research, which are relevant, are necessary and important in a reset or scientific article. Human resources are productive individuals who work as the driving force of an organization, both in institutions and companies that have functions as assets so that they must be trained and developed their abilities. There is no organization or company that does not need human resources, all of which are needed to achieve organizational goals. Not only that, this section also has the obligation and responsibility to develop the organization by applying all organizational values and culture. At the same time, the results of the hypothesis; 1. Motivation affects employee performance 2. Career development affects employee performance 3. Human Resource Planning can affect employee performance 4. The work environment can affect employee performance 5. Leadership style has an influence on employee performance. This research is a literature review raised from various previous studies (previous research) in order to serve as reference material for further studies in the human resources field.